The Abridgements of Sheikh Muhammad Ali Al-Sabouni between Terrified and Praise: Reasons for the difference between him and the Traditional Scholars - Musa, Najwa Hussein Bakkar; Nour, Ahmed Younis bin Haj Mohammed (Journal of Islamic Sciences, 2018)
This study attempts to focus on the abridgements of Sheikh Muhammad Ali Al-Sāboūnī in exegesis and raised controversy between praise and condemnation, criticism and praise as well as the difference between him and the traditional scholars who have alerted that there are some things in the abridgements of Sheikh Al-Sāboūnī appear to be contrary to the method of the sālāf āl-solēh and emerged in his disposition on sect of Ash'ārītē. Only those who are familiar with the field of exegesis and its sciences will appreciate the contribution of Sheikh Muhammad Ali Al-Sāboūnī and respect his efforts in the field of exegesis as well as the value of his writings and works. Indeed, the extent of interest and wide spread of the matters that attract the reader, especially the general readers to permit and easy its terms but it should be noted that it is necessary to differentiate between ahl al-kalam of Ash'arite and those affected by their doctrine. Perhaps the best of argumentation on the senior scholars of Ash'ārītē and those who have been influenced by their doctrine and followed the method of Sheikh Muhammad Ali Al-Sāboūnī and claim that their methods were wrong when its attributes thinking of it, however, they supposed to do not get them out of the fold of Islam. Some of them are senior scholars taken from them in other fields of this matter, but the right in method of characters is the method that the predecessor of this nation of the non-likeness, no representation and no disruption are exactly what should be followed about the abridgements of Sheikh Muhammad Ali Al-Sāboūnī which can be benefited and taken from its. The reader must be aware of because the matters might be different from the method of sālāf āl-solēh in the exegesis.
Keywords: Abridgements; explanation; Al-Sabouni; Terrified; Praise